Counseling Techniques Supporting West African Children With Adverse Childhood Experiences: A Systematic Review - Clay, Shanelle V.; Jackson, Cheria; Stephenson, Quincy (Frontiers in Sociology, 2021)
Using a meta-synthesis approach, through the review of current literature, five published and peer reviewed qualitative research reports were studied. The intention was to identify interventions being used with West African children who have endured adverse childhood experiences. These results were found through matching inclusionary criteria and all studies were screened for appropriateness and relevance to the topic matter. The literature was analyzed across five online databases including Proquest, PsychInfo, Scopus, Wiley, and Springer from January 2005 to June 2020. The authors found minimal evidence indicating interventions used in West Africa for adverse experiences related specifically to children, but found themes related to interventions that serve West African families that include children. Findings were thematically analyzed through meta-synthesis and identified four themes used in the interventions, which include western, spiritual, expressive arts, and cultural approaches. West African children endure adverse experiences such as terrorism, abuse, and war violence that contribute to an increasing the need for mental health interventions. These experiences approached from western, spiritual, expressive arts, and cultural vantage points were identified but limited in information about delivery and efficacy, thus providing little guidance regarding further exploratory research.